Intensive Cleaning Devices for Fire Hoses - Makhkamov, N. Y.; Abdullaev, E. V. (European Journal of Life Safety and Stability (2660-9630), 2023)
Operational and intensive cleaning of various contaminants accumulated in the process of extinguishing fires from fire hoses is possible using a portable intensive wash. Proposed a new device developed by the faculty of the Academy of the Ministry of Emergency Situations of the Republic of Uzbekistan for cleaning the dirt of fire hoses of various hose sections (51, 66, 77).